Production of lactic acid from whey permeates using lactic acid bacteria isolated from cheese. - Waiel F. Sayed (South Valley University, 2020)
The uses of whey permeate for lactic acid production is a dual-purpose process by producing lactic acid and decreasing the environmental pollution problem caused by dumping the lactose- rich dairy byproduct. This study aimed to investigate lactic acid production from whey permeates using lactic acid bacterial isolates. Five isolates from cheese samples were identified as lactobacillus casei MT682513, Enterococcus camelliae MT682510, Enterococcus faecalis MT682509, Enterococcus lactis MT682511, and Wissella paramesenteroides MT682512 using 16S rRNA. Small scale batch fermentations of permeate were conducted under uncontrolled pH conditions. pH, temperature, carbon, and nitrogen sources as well as fermentation time on the conversion rate of lactose to lactic acid were monitored. It was found that Lactobacillus casei exhibited the highest percentage of lactic acid production without any supplementations. The increasing percentage was 107% using glucose (100 gl–1 ) and 44.2 % using yeast extract (10 gl–1 ) as carbon and nitrogen sources, respectively. The optimum lactic acid production was between 30°C and 37°C within a pH value of 6. The highest production of lactic acid under the optimized conditions resulted after 14h of fermentation. This work facilitates further studies of Lactobacillus casei over the optimized conditions of whey parameters on the other industrially important for lactic acid production and applications.